The Development of Feature Radio as a Model in Making Radio Broadcasting Product for English Department Students of State Polytechnic of Padang - Sumira Sumira; Nini Wahyuni (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
This Research and Development (R&D) study discussed about the development of feature radio as the model in making radio broadcasting product for English Department students of State Polytechnic of Padang. The aims of this research is to develop an appropriate model of feature radio that can be used as the standard model in conducting final project. The development was carried out through several steps, namely; needs analysis, product development, product validation, and revision. The needs analysis data were taken from syllabus, academic data, and interview. Meanwhile, the product validation were taken from experts’ judgment. The data were collected through analyzing syllabus, conducting interviews, and giving question-naires. The result of this research is a model of feature radio.Keywords— Feature radio, Research and Development, Pre-production, Production, Post Production